Fortune and Decay of Lexical Expletives in Germanic and Romance along the Adige River - Tomaselli, Alessandra; Bidese, Ermenegildo (Languages (Basel), 2023)
Lexical expletives can be divided into two main classes: (i) CP expletives required by the V2 constraint and, hence, by the necessity to lexicalize the position on the left of the inflected verb and (ii) TP expletives connected with the negative value of the pro-drop parameter and, therefore, with the necessity to lexicalize the ’structural‘ subject position, specifically, [Spec, TP]. The latter can, in turn, be divided into two subclasses: impersonal subjects and positional expletives, which occur with postverbal/low subjects and extraposed subject clauses. While CP expletives only appear in Germanic varieties that maintain V2, the subclassification of TP expletives yields interesting results when comparing Cimbrian and the Venetan varieties in Nord-East Italy, where the gradual disappearance of the positional expletive in free inversion structures and the residual maintenance of impersonal subjects from North to South along the Adige River confirms the distinction between two classes of subject expletives; furthermore, the resilience of impersonal subjects and their distribution in the northwestern part of the area under consideration sheds light on the role of language contact which is confirmed along the same axis—but crucially in the opposite direction—by the increasing employment of cleft constructions in WH-clauses replacing enclisis (i.e.,: pronominal subject inversion with the finite verb).